PERANCANGAN SISTEM INFORMASI PENGUMPULAN LAPORAN TANGGAP DARURAT DARI MASYARAKAT - Ratnasari, Anita; Gata, Grace; Haji, Wachyu Hari; Jumaryadi, Yuwan; Ari Purnadi, Mochamad; Defriansyah; Aqbar, Harry (Journal of Information Systems Management and Digital Business, 2024)
The design of this mobile-based report system is expected to be able to respond quickly to reports from the public for crime prevention, or crime and events that require fast handling such as accidents, fires, kidnappings and other forms of incident and accident that often occur in the community so that they are fast in reporting. This system can make it easier for the authorities to find out the number, type, location of an incident or crime that often occurs in a place, and this system will be automatically connected to the police who will directly monitor reports from users who see directly the incident or incident. Accident in a location so that it can immediately get rescue or help with a fast and appropriate response.